Relationship between workplace incivility and turnover intention: A conceptual framework - Ishak, Wan Zhalkiatul Aida; Ahmad, Fais; Ishak, Khairol Anuar (2017)
The emerging issues that surround the house officers (HO) of Malaysia’s public hospitals has raised significant concerns among the practitioners and the academicians; such as uncivil treatment that occur in the hospital environment.Reflecting from this, this paper aims to discuss the relationship between the workplace incivility and turnover intention among the house officers of Malaysia’s public hospitals.An extensive review provides the insights of the possible relationships between the variables.Related proposed framework of this research is hoped to meet the research objectives and provide valuable insights for future research.